Correlation between the Inflammation Factors and Intima-Media Thickness in Patients with End-Stage Renal Disease (ESRD) on Regular Hemodialysis - Lestariningsih Lestaringsih; Wiguno Projosudjadi; Mochamad Sya’bani; Suharyo Hadisaputro (Cell and BioPharmaceutical Institute, 2019)
Background: Several emerging problems of regular hemodialysis (HD) including cardiovascular complication or atherosclerosis formation caused by chronic inflammation. High sensitive C-reactive protein (hs-CRP) and intima-media thickness (IMT) of the carotid artery can be applied as atherosclerosis progressivity marker. This study was designed to investigate the relationship between some inflammatory factors, including hs-CRP, interleukin (IL)-6, oxidized-low-density lipoproteins (LDL), with IMT among end-stage renal disease (ESRD) patients. This was the first study in Indonesian population. Materials and Methods: This cross-sectional study was performed on ESRD patients who performed regular HD at Hemodialysis Unit of Dr. Kariadi Hospital and Telogorejo Hospital Semarang between October 2009 and April 2010. This was a preliminary report for the cohort study.Results: Seventy-eight HD subjects were enrolled in this study, with mean age of 49.8 years old. Mean HD duration was 25.5±32.16 months. The mean carotid artery wall thickness was 0.64±0.149 mm. IL-6, hs-CRP, and ox-LDL level were higher in IMT group ≥0.5 mm than IMT group <0.5 mm. There was a significant correlation between hs-CRP (prevalence ratio (PR)=1.3; 95% confidence interval (CI)=1.02-1.7; p-value=0.01) as well as IL-6 (PR=1.5; 95% CI=1.1 -2.0; p-value<0.001) and IMT wall thickness. The oxidized-LDL level was not a significant factor to be associated with IMT. The cut-off value for hs-CRP and IL-6 to predict IMT progressivity was 2.8 mg/L and 2.88 mg/L, respectively.Conclusion: There was a significant correlation between IL-6 and hs-CRP levels and IMT. There was not significant correlation between oxidized LDL and IMT.Keywords: hemodialysis, atherosclerosis, IMT, IL-6, hs-CRP, Oxidized-LDL